Characteristics of Daggertooth Pike Conger Fish (Muraenesox cinerus) as Raw Material for Diversification Products Development - Untung Trimo Laksono; Tati Nurhayati; Pipih Suptijah; Nani Nur’aenah; Teguh Setyo Nugroho (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Daggertooth pike conger fish (Muraenesox cinerus) has elongated body shape similar to eels and distribute widely worldwide. The fish has edible portion of 50-60% but there has been less information regarding the chemical characteristics. The aim of this research was to determine chemical composition of daggertooth pike conger fish (proximate, amino acid, fatty acid and mineral) and textural properties from its kamaboko. Purposive sampling method applied in this research with length, freshness and distance from location as criteria. Analytical method performed including proximate, amino acids, fatty acids, and minerals (P, Na, Ca, K, Mg dan Fe). Chemical composition from daggertooth pike conger fish showed that on proximate levels of protein, fat, ash, carbohydrates and moisture content value were 12.273%, 4.96%, 1.17%, 1.12% and 80.49% respectively. Dominant macro minerals, namely potassium (K) 170.20 mg /100 g, Ca 90.75 mg /100 g, and Na 80.15 mg /100 g. Amino acid (AA), namely glutamic acid 2.68%, 1.57% lysine, leusine 1.25%, 1.54% aspartic acid and arginine 1:04%. Moreover, the essential fatty acids namely EPA (eicosa pentanoat acid) 0.6%, DHA (docosa hexanoat acid) 0.9%, 0.2% fatty acids linoleic, oleic and linolenic 1.4% 1.0%. CaCl2 (0.2-0.6%) addition to daggertooth pike conger kamaboko could improve textural quality.